Efeitos da estabilização dos preços nos índices regionais do Brasil: uma análise através da paridade do poder de compra - Saraiva, Tiago Almeida (2012)
This study investigates the effects of inflation stabilization in Brazil in regional price indices through the theory of Purchasing Power Parity. We used the National Index of Consumer Prices Broad, IPCA, covering nine metropolitan regions during the period of 1989 to 2011. We begin our analysis with the test of Perron and Yabu (2009) in order to check for possible structural breaks in the series of real exchange rates between the metropolitan areas. To confirm the hypothesis of Purchasing Power Parity for Brazil, we apply the unit root test ERS (1996) as well as the test of Kim (2000) later modified by Harvey, Leybourne and Taylor (2006) to check for possible changes of persistence in the series. During the period analyzed was detected a decrease of the persistence of the series, we credit this phenomenon to the implement of the Real Plan, showing that price stability positively influence the validation of the hypothesis of Purchasing Power Parity.